Decavanadate Inhibits Mycobacterial Growth More Potently Than Other Oxovanadates - Samart, Nuttaporn; Arhouma, Zeyad; Kumar, Santosh; Murakami, Heide A.; Crick, Dean C.; Crans, Debbie C. (Frontiers in Chemistry, 2018)
51V NMR spectroscopy is used to document, using speciation analysis, that one oxometalate is a more potent growth inhibitor of two bacteria strains than other oxovanadates, thus demonstrating selectivity in its interaction with cells. Historically, oxometalates have had many applications in biological and medical studies, including study of the phase-problem in X-ray crystallography of the ribosome. The effect of different vanadate salts on the growth of Mycobacterium smegmatis (M.smeg) and Mycobacterium tuberculosis (M.tb) was investigated, and speciation was found to be critical for the observed growth inhibition. Specifically, the large orange-colored sodium decavanadate (V10O286-) anion was found to be a stronger inhibitor of growth of two mycobacterial species than the colorless oxovanadate prepared from sodium metavanadate. The vanadium(V) speciation in the growth media and conversion among species under growth conditions was monitored using 51V NMR spectroscopy and speciation calculations. The findings presented in this work is particularly important in considering the many applications of oxometalates in biological and medical studies, such as the investigation of the phase-problem in X-ray crystallography for the ribosome. The findings presented in this work investigate the interactions of oxometalates with other biological systems.